REFORMING MALAYSIA’S DEPORTATION REGIME: DIGITALISATION, INTEGRATION, AND MILITARISATION (Journal of International Studies, 2024)
This paper examines transformations undertaken by the Malaysian government in reforming its deportation policy, operation, and enforcement. It focuses on the post-2008 period during which Malaysia embarked on several reform initiatives, notably the introduction of biometric technology, the implementation of the National Blue Ocean Strategy, and the establishment of a National Task Force under military leadership. This paper aims to analyse the implementation of the reforms and the implications of these initiatives. The analysis draws upon parliamentary debates, ministerial documents, legal texts, online news media and secondary literature. This paper has found the following three findings. First, deportation could be conceptualised as a migration control strategy to achieve zero irregularity. Second, Malaysia’s deportation regime is increasingly technologically driven, integrated, and militarised. Third, Malaysia has established a network of border and migration management databases centred on the identification, monitoring, and surveillance of individuals. The integration of biometrics technology in interior enforcement has led o the emergence of a digital border.